2021
DOI: 10.1002/prp2.885
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between vancomycin AUC/MIC and trough concentration, age, dose, renal function in Chinese critically ill pediatric patients

Abstract: To assess the pharmacokinetic parameters of vancomycin in Chinese critically ill pediatric patients, children treated with vancomycin, hospitalized in the intensive care unit were included. Samples to determine peak and trough serum concentrations were obtained on the third day of treatment. Half‐life was significantly longer in neonates and showed a decreasing trend in infants and children. In patients aged ≥1 month, AUC 24 /MIC ≥400 was achieved in 31.8% at the dose of 40 mg/kg/d, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…However, when it comes to defining a glomerular filtration rate cut-off value to identify an ARC state, it could be seen that there is a wide range of values in the literature. While Chen et al 7 defined ARC as a glomerular filtration rate greater than 130 mL/min/1.73 m 2 , which is accepted as a cut-off value by the vast majority of studies according to the previously done review study,1 Shimamoto et al defined ARC as an estimated glomerular filtration rate of at least 160 mL/min/1.73 m 2 8. Not only is the cut-off value of ARC important, but it is also important how it is measured.…”
Section: Discussionmentioning
confidence: 99%
“…However, when it comes to defining a glomerular filtration rate cut-off value to identify an ARC state, it could be seen that there is a wide range of values in the literature. While Chen et al 7 defined ARC as a glomerular filtration rate greater than 130 mL/min/1.73 m 2 , which is accepted as a cut-off value by the vast majority of studies according to the previously done review study,1 Shimamoto et al defined ARC as an estimated glomerular filtration rate of at least 160 mL/min/1.73 m 2 8. Not only is the cut-off value of ARC important, but it is also important how it is measured.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the Bayesian method is difficult to perform in many hospitals in developing countries, including our hospital, which is a large tertiary teaching hospital, because of a lack of tools and required knowledge. The first-order PK equations to calculate vancomycin AUC would be the next preferred method, but of which there are certain restrictions in children on account of needing collecting 2 steady-state samples to calculate AUC ( 50 , 51 ). Second, according to a systematic review of the correlation between vancomycin trough concentrations and AUC/MIC in children, there is still a lack of research data on the target vancomycin trough concentrations in children, not to mention the target AUC/MIC.…”
Section: Discussionmentioning
confidence: 99%
“…To date, few studies have focused on the association between ARC and AUC 24 /MIC indices. Chen et al [ 28 ] found that AUC 24 /MIC < 400 was more common in pediatric ARC patients from a retrospective cohort of 470 critically ill children. The present study provided evidence in adults with ARC, which is of great value for guiding vancomycin monitoring and individualized medication.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon may be due to the fact that ARC patients tend to have relatively mild organ dysfunction and strong compensatory reserves [ 19 , 21 ]. Although evidence of the direct correlation between ARC and vancomycin treatment failure is limited, ARC has been shown to increase the likelihood of a negative outcome, owing to the clear association with subtherapeutic concentrations and lack of PK/PD target attainment [ 15 , 16 , 17 , 28 ].…”
Section: Discussionmentioning
confidence: 99%